Makna Kekuasaan dalam Interaksi Tokoh Anak pada Film Jumbo (2025): Analisis Semiotika John Fiske - Regina Chintya Zafira Harsono; Choirul Ulil Albab (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Animated films not only function as entertainment media, but can also represent the social dynamics that occur in children’s lives, including power relations within peer groups. This study aims to analyze the representation of power relations in the animated film Jumbo (2025). The study uses a descriptive qualitative approach with John Fiske’s semiotic analysis method which includes three levels of meaning, namely reality, representation, and ideology. Data were obtained through observation and documentation of scenes, dialogue, gestures, facial expressions, and audiovisual elements in the film. The results show that power relations are represented through verbal domination, ridicule, and social exclusion of the character Don as a party who is in a weaker social position in the group. Visually, this inequality is also reinforced through the composition of frames and cinematic techniques that place Don apart from the group. At the ideological level, this film reflects a critique of the normalization of domination in children’s social relationships and emphasizes the importance of empathy, social acceptance, and equality in friendships